First structural characterization of a delocalized, mixed-valent, triangular Cu37+ species: chemical and electrochemical oxidation of a CuII3(mu3-O) pyrazolate and electronic structure of the oxidation product. - Mezei, G; McGrady, J; Raptis, R (2005)
The chemical or electrochemical one-electron oxidation of the all-CuII complex [Cu3(mu3-O)(mu-pz)3X3]2- leads to its formally CuII2CuIII analogue (pz = pyrazolato anion; X = Cl- and PhCOO-). The X-ray single-crystal structure and density functional theory analysis of the latter agree in revealing the delocalized nature of its mixed-valent Cu3(7+) core.